A review on vortex-induced vibrations in confined flows - Duranay, Aytekin; Demirhan, Alkin Erdal; Dobrucali, Erinc; Kinaci, Omer Kemal (Pergamon-Elsevier Science Ltd, 2023)
The response of structures to Vortex-induced vibrations (VIV) is heavily influenced by the type of confinement of the surrounding bodies. The vortex patterns and motion responses are highly dependent on factors such as the finite aspect ratio, tip effects, characteristics of 3D flow, proximity to a bottom boundary layer, and piercing cylinders or proximity to a free surface. The response of these bodies in confined waters is significantly altered, which can be investigated in terms of the fluctuating lift, drag, amplitude, frequency, Strouhal number, and the phase difference between oscillations and vortex shedding. A physical explanation of these ingredients and a way out for the corresponding problems have been discussed in the literature individually or given as a review of certain parts. In the present review, we have aimed to compile all the ingredients of the confinement types on VIV including the physical meaning and effects on the structures. The paper is structured as follows: in the first part the introduction is given, in the second part physical explanation of VIV in confined flows is discussed, and in the third part the ingredients of confinement are divided into three main categories. The main categories are separated as finiteness or aspect ratio effect on VIV regarding end conditions - tip effects - free end, free surface effect, and effect of bottom or proximity of plane. Finally, some important points of these VIV studies are underlined.
Keywords: VIV; Aspect ratio; Tip effects; Free surface effects; Bottom effects; Confinement of VIV